Domestic Violence: Comparison between Islamic Law and Domestic Violence - Hanafi Hanafi; Hidayatullah Hidayatullah; Tamjidnor Tamjidnor (LAFADZ JAYA Publisher, 2022)
The purpose of this study was to determine the comparison between Islamic Law and Domestic Violence Law in handling domestic violence in Indonesia. The type of research used is qualitative research with comparative descriptive method. As the only research design, the ethnographic method is the method in this research with descriptive analysis writing techniques, where ethnography itself provides a tool that allows the research process to take place better. The results of this study are from two sources of law, namely Islamic Law and Domestic Violence Law which can be used as a legal basis to punish and limit the arbitrariness of a husband against his wife and family members. In addition, the two sources of law view the need for formal juridical protection of a person's human rights and freedoms, preventing arbitrary acts of violating other people's laws without clear or justified reasons. The conclusion of this study is that there is a relationship between Islamic Law and the Domestic Violence Law, including 1) The views of Islamic law and positive law view that domestic violence or violence against wives is a despicable and promiscuous behavior; 2) Correlation about the purpose of punishment; 3) In terms of punishment, it can be said that punishment in the form of imprisonment is a form of takfir punishment in Islamic criminal law.